Long-term safety and efficacy of extended-interval prophylaxis with recombinant factor IX Fc fusion protein (rFIXFc) in subjects with haemophilia B - Pasi, K John; Fischer, Kathelijn; Ragni, Margaret; Nolan, Beatrice; Perry, David J; Kulkarni, Roshni; Ozelo, Margareth; Mahlangu, Johnny; Shapiro, Amy D; Baker, Ross I; Bennett, Carolyn M; Barnes, Christopher; et al. (Thrombosis and haemostasis, 2017)
The safety, efficacy, and prolonged half-life of recombinant factor IX Fc fusion protein (rFIXFc) were demonstrated in the Phase 3 B-LONG (adults/adolescents ≥12 years) and Kids B-LONG (children <12 years) studies of subjects with haemophilia B (≤2 IU/dl). Here, we report interim, long-term safety and efficacy data from B-YOND, the rFIXFc extension study. Eligible subjects who completed B-LONG or Kids B-LONG could enrol in B-YOND. There were four treatment groups: weekly prophylaxis (20-100 IU/kg every 7 days), individualised prophylaxis (100 IU/kg every 8-16 days), modified prophylaxis (further dosing personalisation to optimise prophylaxis), and episodic (on-demand) treatment. Subjects could change treatment groups at any point. Primary endpoint was inhibitor development. One hundred sixteen subjects enrolled in B-YOND. From the start of the parent studies to the B-YOND interim data cut, median duration of rFIXFc treatment was 39.5 months and 21.9 months among adults/adolescents and children, respectively; 68/93 (73.1 %) adults/adolescents and 9/23 (39.1 %) children had ≥100 cumulative rFIXFc exposure days. No inhibitors were observed. Median annualised bleeding rates (ABRs) were low in all prophylaxis regimens: weekly (≥12 years: 2.3; <6 years: 0.0; 6 to <12 years: 2.7), individualised (≥12 years: 2.3; 6 to <12 years: 2.4), and modified (≥12 years: 2.4). One or two infusions were sufficient to control 97 % (adults/adolescents) and 95 % (children) of bleeding episodes. Interim data from B-YOND are consistent with data from B-LONG and Kids B-LONG, and confirm the long-term safety of rFIXFc, absence of inhibitors, and maintenance of low ABRs with prophylactic dosing every 1 to 2 weeks.